PRaG Therapy of Refractory Metastatic Gastric Cancer: A Case Report - Xu, Hong; Hong, Zhihui; Xu, Meiling; Kong, Yuehong; Ma, Yifu; Shan, Chanchan; Xing, Pengfei; Zhang, Liyuan (Frontiers in Immunology, 2022)
Patients with metastatic gastric cancer had limited treatments and often had a somber prognosis, especially when patients were unable to tolerate high-intensity cytotoxic treatment due to poor physical condition or organ dysfunction after the failure of standard therapy. Here, we reported a metastatic and proficient mismatch repair (pMMR) gastric adenocarcinoma patient with the Eastern Cooperative Oncology Group (ECOG) performance status score of 2 associated with hypoproteinemia and fatigue, and poor appetite that was unable to tolerate high-intensity therapy after several chemotherapy regimens and anti-angiogenic therapy. After receiving novel triple-combination therapy, which consists of PD-1 inhibitor, Radiotherapy and Granulocyte-macrophage colony-stimulating factor (GM-CSF) therapy (PRaG for short), the patient achieved a complete response (CR) with a progression-free survival time of 14 months, and ECOG performance status score improved from 2 to 0. A significant systemic effect was observed in this case and the PRaG triple-combination therapy might provide a novel treatment strategy for metastatic pMMR gastric cancer patients.